2022
DOI: 10.3390/ijms23041926
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Blood-Based Diagnostics to Predict Tumor Biology and Extend the Application and Personalization of Radiotherapy in Liver Cancers

Abstract: While the incidence of primary liver cancers has been increasing worldwide over the last few decades, the mortality has remained consistently high. Most patients present with underlying liver disease and have limited treatment options. In recent years, radiotherapy has emerged as a promising approach for some patients; however, the risk of radiation induced liver disease (RILD) remains a limiting factor for some patients. Thus, the discovery and validation of biomarkers to measure treatment response and toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
(169 reference statements)
0
1
0
Order By: Relevance
“…However, studies have found that the prediction accuracy of these models is limited [ 8 , 9 , 10 ]. As a non-invasive method, a blood-based biomarker analysis is more attractive for various cancers [ 11 , 12 ]. At the same time, much evidence suggests that clinical factors alone are not sufficient to predict the survival rate of patients with UC, and the systemic inflammatory response and nutritional deficiency might play a vital role in the development and progression of cancer [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have found that the prediction accuracy of these models is limited [ 8 , 9 , 10 ]. As a non-invasive method, a blood-based biomarker analysis is more attractive for various cancers [ 11 , 12 ]. At the same time, much evidence suggests that clinical factors alone are not sufficient to predict the survival rate of patients with UC, and the systemic inflammatory response and nutritional deficiency might play a vital role in the development and progression of cancer [ 13 ].…”
Section: Introductionmentioning
confidence: 99%